Investigation of Epoxy Resin Effect as Additional Component on the Mechanical Properties of Polymer Concrete - Kardianto, Arie; Elvira, Elvira; Herwani, Herwani; Nurhayati, Nurhayati (Fakultas Teknik Universitas Tanjungpura, 2025)
This research investigates the mechanical properties of polymer concrete, a composite material composed of varying proportions of epoxy resin, sand, and crushed stone. A total of 76 cylindrical specimens were prepared and tested for compressive strength, split tensile strength, and elastic modulus over curing durations of 1, 2, 7, and 14 days. The results indicated that the highest compressive strength of 44.78 MPa was achieved by a specimen with 34% epoxy resin and 66% crushed stone after 1 day of curing. In contrast, the lowest strength was found in mixtures with high sand content and lower resin proportions. The split tensile strength increased with the addition of crushed stone, reaching a peak value of 1.69 MPa at 14 days. Furthermore, the elastic modulus improved as the coarse aggregate content increased, with a maximum value of 4,538.50 MPa. These findings highlight the potential of epoxy-based polymer concrete as a viable alternative to conventional cement concrete, particularly for rapid-strength applications. The results also provide a foundation for optimizing mixture design in structural applications, contributing to the development of high-performance composite materials in civil engineering.